Analisis Faktor-Faktor Yang Mempengaruhi Minat Siswa SMA/SMK Mendaftar Di STMIK Sinar Nusantara Surakarta - Sanggrama Anuraga, Muhammad Hasbi, Tri Irawati (Jurnal Ilmiah SINUS, 2013)
The research to determine the influence of interest, excitement, liveliness or vocational high school students enroll in STMIK Sinar Nusantara Surakarta. This study uses descriptive correlation. Methods of data collection using questionnaires and documentation. The population in this study were all students at STMIK Sinar Nusantara in Surakarta using purposive sampling method by 80 respondents representative. Based on the available data concluded that there are significant interest and pleasure factor. Whereas no effect on the activity of registering interest in STMIK Sinar Nusantara. By registering silmultan the influence of 57.9%Key words   :   interest, excitement, liveliness, student enroll